Fear of Crime and Post-Traumatic Stress Disorder Treatment: Investigating Indonesian’s Pedophilia Cases - Nurbayani, Siti; Dede, Moh; Malihah, Elly (SCAD Independent, 2022)
Pedophilia is a part of child abuse that tends to occur in children surrounding environment. Pedophiles are not only about trauma but create a sexual predator cycle when the victims are not managed properly. This study aimed to analyze the fear of crime and post-traumatic stress disorder treatment in pedophilia cases in Indonesia. As qualitative research, data was obtained using observation and interview activities for one year continuously for each area of interest. This study was held in three regions in Java, Indonesia, which were specific locations of the victims’ residence in Sudajaya Hilir (Sukabumi City, West Java), Cintanagara (Garut Regency, West Java), and Sukamanah (Tangerang Regency, Banten). This study showed that fear of crime from the victims' parents and families is still low. It can be seen from those who tend to give full trust to the suspects because closely and consider like good people. In Garut and Sukabumi's cases, inappropriate post-traumatic disorder treatment caused the victims to transform into sexual predators. Pedophilia made the fear of crime in society, where the suspects have similar images as good and undangerous people for children. Not ideal post-traumatic stress disorder treatment is proven to cause the sexual predator cycle.